PsycEXTRA Dataset 2013
DOI: 10.1037/e586222013-001
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Sampling Study of PTSD and Alcohol-Related Problems

Abstract: Posttraumatic stress disorder (PTSD) represents a debilitating psychiatric condition that is affecting the lives of many returning veterans. PTSD and alcohol use and dependence are highly comorbid. The purpose of this study was to understand the functional mechanisms between PTSD and alcohol use and problems. Specifically, the role of negative urgency and emotional intelligence were investigated as vulnerability and resiliency factors, respectively. This study utilized experience sampling to test associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
5
10
0
Order By: Relevance
“…Nonetheless, researchers are often interested in not only assessing number of drinks in these studies but also assessing predictors such as affect, which may be more influenced by memory biases or establishing temporal associations within days, in which case experience sampling approaches may be necessary. A combination of experience sampling and daily morning reports (Gaher et al, 2014; Simons et al, 2010, 2014) or use of EMA (Piasecki et al, 2011) may be necessary to accurately assess low intensity drinking events.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, researchers are often interested in not only assessing number of drinks in these studies but also assessing predictors such as affect, which may be more influenced by memory biases or establishing temporal associations within days, in which case experience sampling approaches may be necessary. A combination of experience sampling and daily morning reports (Gaher et al, 2014; Simons et al, 2010, 2014) or use of EMA (Piasecki et al, 2011) may be necessary to accurately assess low intensity drinking events.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have linked PTSD severity to alexithymia, defined as the inability to identify or describe one's emotions (McCaslin et al, 2006). In a recent study of OEF/OIF veterans, higher emotional intelligence (defined as the ability to understand and regulate emotions) predicted overall fewer symptoms of PTSD, less alcohol use, and alcohol problems (Gaher et al, 2014). Another study of college students found that several emotion dysregulation facets including impulse control difficulties and lack of emotional clarity were associated with the number of negative consequences of alcohol use (Dvorak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…an individual may take in response to intense negative affect (Cyders & Smith, 2008) and has been independently associated with greater rates of PTSD (Weiss et al, 2013) and alcohol-related problems in previous research (Settles, Cyders, & Smith, 2010; Wray, Simons, Dvorak, & Gaher, 2012; Kaiser, Milich, Lynam, & Charnigo, 2012; Shishido et al, 2013). Indeed, prospective research shows that posttraumatic stress symptoms are associated with, and predict, higher rates of future alcohol-related problems (Gaher et al, 2014; Hooper et al, 2008; Ouimette, Read, Wade, & Tirone, 2010). Due to the high comorbidity between PTSD and alcohol-related problems, it is essential to study PTSD and alcohol outcomes together in the same model and identify mechanisms to better understand the high comorbidity.…”
Section: Introductionmentioning
confidence: 99%